Answer:
D
Step-by-step explanation:
36x² - 49 ← is a difference of squares and factors in general as
a² - b² = (a - b)(a + b)
then
36x² - 49
= (6x)² - 7²
= (6x - 7)(6x + 7)
Thus 6x - 7 is a factor of the expression
The correct answer is; 14x +4
Answer:
=
Step-by-step explanation:
Students use the least squares regression line to make predictions. ... Example 1 (2 minutes): Using a Line to Describe a Relationship ... the model given in the student lesson to predict a man's height using a shoe length of ... Below is a scatter plot of the data with two linear models, ... in Exercise 3 that represents this man
ANSWER
![-48-25i](https://tex.z-dn.net/?f=-48-25i)
EXPLANATION
We want to simplify the expression,
![(-19+7i) - (29+32i)](https://tex.z-dn.net/?f=%28-19%2B7i%29%20-%20%2829%2B32i%29)
Let us expand the bracket to obtain,
![-19+7i-29-32i](https://tex.z-dn.net/?f=-19%2B7i-29-32i)
We now group the complex number parts and real number parts.
![-19 -29+7i-32i](https://tex.z-dn.net/?f=-19%20-29%2B7i-32i)
We simplify further to obtain,
![- 48-25i](https://tex.z-dn.net/?f=-%2048-25i)
This is in the form,
![a+bi](https://tex.z-dn.net/?f=a%2Bbi)
where
![a=-48](https://tex.z-dn.net/?f=a%3D-48)
and